2003
DOI: 10.1097/01.mp.0000052375.72841.e2
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Analysis of Atypical Lesions in Image-Guided Core Breast Biopsies

Abstract: Stereotactic or ultrasound-guided needle core breast biopsies (NCBB) are now routinely performed to assess suspicious microcalcifications or non-palpable masses detected by screening mammography. This approach has been shown to have high sensitivity and specificity in establishing the diagnosis of fibrocystic lesions, ductal carcinoma in situ (DCIS), and invasive carcinoma (1). As more NCBB are being performed, pathologists are encountering lesions with features of atypical ductal hyperplasia (ADH) or atypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 14 publications
3
41
0
2
Order By: Relevance
“…Little is known about the underlying biology of microcalcifications in pre-neoplastic and pre-invasive lesions. However, since the microcalcifications that occur in CCLs are indistinguishable radiologically from those seen in atypical ductal hyperplasia (ADH; DIN1b) and ductal carcinoma in situ (DCIS), needle biopsy or excision is required for diagnosis [3,4,7,37]. The increased incidence of CCLs may reflect improved recognition by pathologists or reflect the increasing representation of biopsies generated by mammographic screening.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the underlying biology of microcalcifications in pre-neoplastic and pre-invasive lesions. However, since the microcalcifications that occur in CCLs are indistinguishable radiologically from those seen in atypical ductal hyperplasia (ADH; DIN1b) and ductal carcinoma in situ (DCIS), needle biopsy or excision is required for diagnosis [3,4,7,37]. The increased incidence of CCLs may reflect improved recognition by pathologists or reflect the increasing representation of biopsies generated by mammographic screening.…”
Section: Introductionmentioning
confidence: 99%
“…A few small studies (less than 40 cases) (almost all published in abstract form) were confused and showed a more advanced lesion, either DCIS or IC, in between 0 and 30% of cases of subsequent surgical excision after FEA diagnosed with CNB [4,[15][16][17][18][19][20][21]. Thus, published studies are rare, lack standardized terminology and sometimes confuse FEA and ADH on pathology [4,16].…”
Section: As Defined By the World Health Organization (Who) Working Grmentioning
confidence: 99%
“…80 In another review, several subsets of patients with a diagnosis of ADH on CNB with a high likelihood of DCIS in subsequent surgical excisions were identified. 81 These included patients in whom the CNB was diagnosed as ADH bordering on DCIS and patients with a diagnosis of ADH with papillary features, with a 63% and 36% likelihood of DCIS in subsequent surgical biopsies, respectively. The number of atypical foci in CNB and the mammographic span of the microcalcifications, greater than four foci and greater than 2 cm, also correlated with an increased likelihood of DCIS on excision.…”
Section: Should a Mammogram Be Performed Following A Core Biopsy Procmentioning
confidence: 99%
“…The number of atypical foci in CNB and the mammographic span of the microcalcifications, greater than four foci and greater than 2 cm, also correlated with an increased likelihood of DCIS on excision. 81 What is the accuracy of predicting invasion by stereotactic core biopsy?…”
Section: Should a Mammogram Be Performed Following A Core Biopsy Procmentioning
confidence: 99%